Genetic diversity for adult plant resistance to leaf rust in bread wheat (Triticum aestivum L.) - Mishra, A.N.; Kaushal, K.; Dubey, V.G.; Prasad, S.V. Sai (The Indian Journal of Genetics and Plant Breeding, 2016)
There is an increasing worldwide interest in adult plant resistance (APR) since most examples of durable resistance to leaf rust in wheat are this kind. Twelve bread wheat genotypes were studied for inheritance of APR to leaf rust using pathotype 77-5 (121R63-1), the most prevalent and widely virulent one on bread wheat germplasm in India. Resistance was controlled by a pair of dominant and recessive genes each in CPAN 1676 and CSP 44 and by two independent dominant genes each in CPAN 1796,Frontana, HD 2009,HD 2135,HUW 37,HW 517,Nainari 60,Pavon 76,VL 404 and WG 138. Segregation patterns observed in their intercrosses showed the presence of at least four genes, including a recessive one, among these genotypes in addition to known APR genes Lr34, Lr46, Lr48, Lr49 and Lr68. The present findings are expected to contribute toward enriching diversity for leaf rust resistance in bread wheat improvement programmes.